Calling Power to Account : Law, Reparations, and the Chinese Canadian Head tax. - Dyzenhaus, David (University of Toronto Press, 2005)
Calling Power to Account suggests that our legal systems can hope to play a part in responding to their own legacy of past injustice only when they recognize the full array of issues posed by the Head Tax Case.